The Power of Shopee Live Streaming on Z Generation Purchasing Decisions - Sri Hardianti Sartika; Kurniawan Kurniawan (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2023)
The focus of the research is to determine the power of live streaming carried out by shops selling on Shopee on product purchasing decisions by Generation Z. Quantitative methods using survey data collection techniques are used to explain this phenomenon. The instrument used was 15 question items consisting of 9 items about live streaming variables and six items about purchasing decisions, then packaged in a Google Form questionnaire and distributed via social media. The sample in this study consisted of 185 respondents aged 13 – 26 years (generation Z). The data obtained was then analyzed using descriptive and differential statistics to determine the relationship between variables. Statistical data analysis using SPSS version 25. The results show that Shopee Live Streaming contributes 62% to Z Generation Purchasing Decisions. So it provides information that live streaming activities can attract consumers to buy, the seller's products can reach a wider market, educate consumers directly about the products offered by the seller, and increase immediate feedback.